The Social Business Model Canvas Based on Baitulmaal: Case Study of Gerakan Indonesia Beras Baitulmaal Munzalan Indonesia Yogyakarta - Putri, Diandra Aqila (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
This study analyzes the implementation of the Social Business Model Canvas (SBMC) in the Gerakan Infaq Beras (GIB) program by Baitulmaal Munzalan Indonesia, Yogyakarta Branch. Using a descriptive qualitative method, the research examines the 13 key components of the SBMC: Social Value Proposition, Impact Measures, Customer Value Proposition, Beneficiaries, Customers, Type of Intervention, Channels, Key Activities, Key Resources, Key Partners and Stakeholders, Cost Structure, Revenue, and Surplus. The findings reveal that GIB Yogyakarta successfully distributes over 25 tons of rice monthly to more than 21,000 students across 300 pesantren (Islamic boarding schools). The program adheres to the principle of